Inotersen to Treat Polyneuropathy Associated with Hereditary Transthyretin (hATTR) Amyloidosis - Christopher Robinson; Cynthia Pham; Alec M. Zamarripa; Chase S. Dugay; Christopher A. Lee; Amnon A. Berger; Avi Landman; Elyse M. Cornett; Hisham Kassem; Alan D. Kaye; Ivan Urits; Omar Viswanath; et al. (Health Psychology Research)
# Background